Engagement and Graduation in Text of the Law on Electronic Information and Transaction - Surbakti, E B; Sinar, T S; Setia, E; ., Suriyadi (KnE Social Sciences, 2018)
The objective of this study was to describe the pattern of Engagement and Graduation in text of UU ITE (the Law of the Republic of Indonesia No. 11/2008 on Electronic Information and Transaction). The data were collected from the text transcript of UU ITE. This study employed the theory of Systemic Functional Linguistics with parameter of category of Appraisal. The data were analyzed, distributed and interpreted to observe the status and type of semantic and grammatical means of categories found in the context of the discourse based on the Appraisal framework. The results of the study demonstrated that (1) the pattern of the lexical means conveying positioning used in the text of UU ITE tended to be Engagement ∧ Heterogloss ∧ Intra-vocalization ∧ Open ∧ Modality. Based on the design form or structure, the lexical means conveying Engagement in UU ITE was dominantly found in Chapter VII on prohibited actions and in Chapter III on electronic information, document and signature (2) the pattern of the lexical means conveying Graduation used in the text of UU ITE tended to be Graduation ∧ Force ∧ Quantification ∧ Time. According to the design form and structure, the lexical means conveying Graduation in UU ITE was dominantly found in Chapter XI on criminal provisions. Keywords: engagement, graduation, UU ITE, modality.